Helper T Cells in Idiopathic Membranous Nephropathy - Zhao, Qihan; Dai, Haoran; Liu, Xianli; Jiang, Hanxue; Liu, Wenbin; Feng, Zhendong; Zhang, Na; Gao, Yu; Dong, Zhaocheng; Zhou, Xiaoshan; Du, Jieli; Zhang, Naiqian; et al. (Frontiers in Immunology, 2021)
Idiopathic membranous nephropathy (IMN) is an autoimmune disease in which the immune system produces an antibody response to its own antigens due to impaired immune tolerance. Although antibodies are derived from plasma cells differentiated by B cells, the T-B cells also contribute a lot to the immune system. In particular, the subsets of helper T (Th) cells, including the dominant subsets such as Th2, Th17, and follicular helper T (Tfh) cells and the inferior subsets such as regulatory T (Treg) cells, shape the immune imbalance of IMN and promote the incidence and development of autoimmune responses. After reviewing the physiological knowledge of various subpopulations of Th cells and combining the existing studies on Th cells in IMN, the role model of Th cells in IMN was explained in this review. Finally, the existing clinical treatment regimens for IMN were reviewed, and the importance of the therapy for Th cells was highlighted.